Anisotropic conductive member and joint body
The anisotropic conductive member addresses the issue of buckling conduction paths by incorporating a controlled protrusion structure, enhancing bonding strength and preventing short circuits while ensuring reliable electrical conductivity.
Patent Information
- Application Number
- JP2024053707
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2044-03-28
AI Technical Summary
Conventional anisotropic conductive bonding members often experience buckling of conduction paths during bonding, leading to insufficient bonding strength and potential short circuits.
The development of an anisotropic conductive member with a specific structure, featuring conductive paths that protrude from the insulating substrate with a controlled arithmetic average distance between top and contact portions, ranging from 2 nm to 200 nm, to suppress buckling and ensure stable bonding.
This solution effectively suppresses buckling of the conduction paths, achieving sufficient bonding strength and preventing short circuits, while maintaining reliable electrical conductivity.
Smart Images

Figure 0007649400000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an anisotropically conductive member and a bonded body having a plurality of conductive paths each having a protrusion that penetrates an insulating substrate in the thickness direction and protrudes from at least one surface of the insulating substrate, and in particular to an anisotropically conductive member and a bonded body in which the surface of the insulating substrate from which the protrusions protrude has a plurality of apexes and a plurality of contact portions at which the protrusions are in contact with the insulating substrate. [Background technology]
[0002] 2. Description of the Related Art There is an anisotropic conductive member having conductive paths in which a plurality of through holes are provided in an insulating base material and filled with a conductive material such as a metal. Anisotropically conductive members are widely used as electrical connection members for electronic components such as semiconductor elements, etc., and as inspection connectors for carrying out functional tests, because electrical connection between the electronic component and the circuit board can be obtained simply by inserting the anisotropically conductive member between the electronic component and the circuit board and applying pressure therebetween. In particular, electronic components such as semiconductor elements are being significantly downsized. Conventional methods for directly connecting wiring boards, such as wire bonding, flip chip bonding, and thermocompression bonding, may not be able to fully ensure the stability of electrical connections of electronic components, and therefore anisotropic conductive materials have been attracting attention as electronic connection materials.
[0003] As an anisotropic conductive member, for example, Patent Document 1 describes an anisotropic conductive bonding member having an insulating base material made of an inorganic material, a plurality of conductive paths made of a conductive member, and a resin layer provided on the entire surface of the insulating base material. The conductive paths are provided penetrating the insulating base material in the thickness direction while being insulated from each other. The conductive paths are parallel to each other and have protruding parts protruding from the surface of the insulating base material, and the ends of the protruding parts are embedded in the resin layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-037509 A Summary of the Invention [Problem to be solved by the invention]
[0005] When the anisotropic conductive bonding member of Patent Document 1 is used as an electronic connection member, the conductive paths of the anisotropic conductive bonding member are bonded to the electrodes of the semiconductor element to be connected, etc. During bonding, the protruding portions of the conductive paths that protrude from the surface of the insulating base material may buckle. If the protruding portion of the conductive path buckles during bonding, the bonding between the conductive path and the electrode of the semiconductor element or the like may become insufficient, and sufficient bonding strength may not be obtained. For this reason, it is desirable to prevent the conductive path from buckling. An object of the present invention is to provide an anisotropically conductive member and a bonded body in which buckling of the conductive paths is suppressed. [Means for solving the problem]
[0006] In order to achieve the above-mentioned object, invention [1] is an anisotropic conductive member comprising an electrically insulating substrate, and a plurality of conductive paths penetrating the insulating substrate in a thickness direction, being electrically insulated from one another, and having protrusions protruding from at least one surface of the insulating substrate, wherein in a cross section in the thickness direction of the insulating substrate, the surface of the insulating substrate from which the protrusions of the conductive paths protrude has a plurality of apexes, and each of the plurality of protrusions has a contact portion in contact with the insulating substrate, and the arithmetic mean distance in the thickness direction between the plurality of contact portions and the plurality of apexes is 2 nm to 200 nm.
[0007] Invention [2] is the anisotropic conductive member according to invention [1], in which the conductive paths are made of Cu, Au or Al. Invention [3] is the anisotropic conductive member according to invention [1] or [2], in which, when the diameter of the protrusion is d and the length of the protrusion in the thickness direction of the insulating substrate is h, d / h is 0.1 to 20. An invention [4] is the anisotropically conductive member according to any one of inventions [1] to [3], wherein the length of the protrusion in the thickness direction of the insulating base material is 6 to 6000 nm.
[0008] Invention [5] is a bonded body in which an anisotropically conductive member and a member to be bonded are bonded, and a resin is filled between the anisotropically conductive member and the member to be bonded. The anisotropically conductive member has an electrically insulating base material and a plurality of conductive paths which penetrate the insulating base material in the thickness direction and are provided in a state in which they are electrically insulated from each other and have protrusions protruding from at least one surface of the insulating base material. In a cross section in the thickness direction of the insulating base material, the surface of the insulating base material from which the protrusions of the conductive paths protrude has a plurality of apexes, and the plurality of protrusions each have a contact portion in contact with the insulating base material, and the arithmetic mean distance in the thickness direction between the plurality of contact portions and the plurality of apexes is 2 nm to 200 nm. Invention [6] is the joined body according to invention [5], in which the joined members have a metal layer and a resin layer, and the metal layer is exposed from the resin layer. Invention [7] is the joined body according to invention [5], in which the joined members have a plurality of metal layers, and at least one of the plurality of metal layers has a different height. Invention [8] is a joined body according to the invention [6], in which the joined members have a joining surface on which a plurality of metal layers are provided, and the area of the joining surface is larger than the area of the surface from which the protruding portion of the anisotropic conductive member protrudes. Effect of the Invention
[0009] According to the present invention, it is possible to provide an anisotropically conductive member and a bonded body in which buckling of the conductive path is suppressed. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view illustrating an example of an anisotropically conductive member according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic plan view illustrating an example of an anisotropically conductive member according to an embodiment of the present invention. [Diagram 3]1 is a schematic cross-sectional view showing an enlarged portion of an example of an anisotropically conductive member according to an embodiment of the present invention. [Figure 4] FIG. 1 is a schematic cross-sectional view showing a first example of a bonded body according to an embodiment of the present invention. [Diagram 5] 1 is a schematic cross-sectional view showing an enlarged portion of a first example of a bonded body according to an embodiment of the present invention. [Figure 6] 1A to 1C are schematic cross-sectional views showing a manufacturing method of a first example of a bonded body according to an embodiment of the present invention. [Figure 7] FIG. 4 is a schematic cross-sectional view showing an enlarged portion of a second example of a bonded body according to an embodiment of the present invention. [Figure 8] 2 is a schematic cross-sectional view showing one step of an example of a method for producing an anisotropically conductive member according to an embodiment of the present invention. FIG. [Figure 9] 2 is a schematic cross-sectional view showing one step of an example of a method for producing an anisotropically conductive member according to an embodiment of the present invention. FIG. [Figure 10] 2 is a schematic cross-sectional view showing one step of an example of a method for producing an anisotropically conductive member according to an embodiment of the present invention. FIG. [Figure 11] 2 is a schematic cross-sectional view showing one step of an example of a method for producing an anisotropically conductive member according to an embodiment of the present invention. FIG. [Figure 12] 2 is a schematic cross-sectional view showing one step of an example of a method for producing an anisotropically conductive member according to an embodiment of the present invention. FIG. [Figure 13] 2 is a schematic cross-sectional view showing one step of an example of a method for producing an anisotropically conductive member according to an embodiment of the present invention. FIG. [Figure 14] 2 is a schematic cross-sectional view showing one step of an example of a method for producing an anisotropically conductive member according to an embodiment of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] BEST MODE FOR CARRYING OUT THE DISCLOSURE The anisotropically conductive member and bonded body of the present invention will be described in detail below with reference to the preferred embodiments shown in the accompanying drawings. It should be noted that the drawings described below are illustrative for explaining the present invention, and are simplified or exaggerated for explaining the present invention, and therefore the present invention is not limited to the drawings shown below. In the following, the range of values indicated by "~" includes the values written on both sides. For example, when ε is the value ε α ~number ε β That is, the range of ε is the number ε α and the number ε α The range includes ε α ≦ε≦ε α It is. Unless otherwise specified, the parallel and perpendicular directions include error ranges generally accepted in the relevant technical field. Unless otherwise specified, the temperature, time and pressure include error ranges generally accepted in the relevant technical field. In addition, the term "same" includes a generally acceptable margin of error in the relevant technical field. In addition, the terms "over the entire surface" and "over the entire surface" include a generally acceptable margin of error in the relevant technical field. The anisotropically conductive member and the bonded body will be specifically described below.
[0012] [Example of anisotropic conductive material] Fig. 1 is a schematic cross-sectional view showing an example of an anisotropically conductive member according to an embodiment of the present invention. Fig. 2 is a schematic plan view showing an example of an anisotropically conductive member according to an embodiment of the present invention. Fig. 3 is a schematic cross-sectional view showing an enlarged portion of the example of an anisotropically conductive member according to an embodiment of the present invention. Fig. 1 and Fig. 3 show a cross section in a thickness direction Dt of the insulating base material 20. Fig. 2 is a plan view seen from the front surface 20a side of the insulating base material 20 in Fig. 1, showing a state in which the resin layer 24 is not present. 1 includes an insulating substrate 20 having electrical insulation properties, and a plurality of conductive paths 22 that penetrate the insulating substrate 20 in a thickness direction Dt, are provided in a state in which they are electrically insulated from one another, and have protruding portions that protrude from at least one surface. Also, the anisotropically conductive member 10 includes a resin layer 24 that covers at least one surface of the insulating substrate 20. The anisotropically conductive member 10 is conductive in the thickness direction Dt of the insulating substrate 20. In the anisotropically conductive member 10, the resin layer 24 is not necessarily required, and the anisotropically conductive member 10 may have a configuration without the resin layer 24.
[0013] The conductive paths 22 are provided in the insulating base material 20 in a state in which they are electrically insulated from one another. In this case, for example, the insulating base material 20 has a plurality of pores 21 penetrating in the thickness direction Dt. The conductive paths 22 are provided in the plurality of pores 21. The conductive paths 22 protrude from the front surface 20a of the insulating base material 20. The conductive paths 22 also protrude from the back surface 20b of the insulating base material 20. The conductive paths 22 may protrude from one surface of the insulating base material 20 in the thickness direction Dt. For example, a resin layer 24 is provided on the surface of the insulating base material 20 from which the conductive paths 22 protrude. The resin layer 24 covers the protruding portion 22a of the conductive paths 22, and the protruding portion 22a is embedded in the resin layer 24. The resin layer 24 also covers the protruding portion 22b of the conductive paths 22, and the protruding portion 22b is embedded in the resin layer 24. The insulating base material 20 is made of, for example, an anodized film. The anodized film is formed, for example, by anodizing a valve metal. The front surface 20a of the insulating base material 20 and the back surface 20b of the insulating base material 20 are surfaces that face each other in the thickness direction Dt of the insulating base material 20.
[0014] The anisotropically conductive member 10 has anisotropic conductivity and has conductivity in the thickness direction Dt as described above, but has sufficiently low conductivity in the direction x parallel to the surface 20a of the insulating base material 20. The direction x is a direction perpendicular to the thickness direction Dt. The anisotropically conductive member 10 has, for example, a circular outer shape as shown in Fig. 2. The outer shape and size of the anisotropically conductive member 10 are appropriately determined according to the application, etc., and the outer shape may be, for example, a square. For example, the anisotropically conductive member 10 is bonded in a state where there is no resin layer 24, or in a state where there is a resin layer 24 but nothing is present on the surface 24a.
[0015] 3, the surface 20a of the insulating substrate 20 is not flat but has an uneven configuration. There are a plurality of recesses 20d on the surface 20a of the insulating substrate 20. A recess 20d is provided for each conductive path 22. The recesses 20d are arranged so as to surround the conductive path 22 with the conductive path 22 at the center. In a cross section of insulating substrate 20 in thickness direction Dt shown in FIG. 3, the surface of insulating substrate 20 from which protrusions 22a protrude, that is, front surface 20a in FIG. 3, has a plurality of apexes Pc and a plurality of contact portions Vc.
[0016] The apex Pc is a high portion of the surface of the insulating base material 20 on the protruding portion 22a side in a cross section in the thickness direction Dt of the insulating base material 20. The apex Pc is, for example, a boundary portion between adjacent recesses 20d. The contact portion Vc is a portion where each of the multiple protrusions 22a contacts the insulating substrate 20 in a cross section in the thickness direction Dt of the insulating substrate 20. The contact portion Vc is located at the end of the protrusion 22a on the insulating substrate 20 side. More specifically, the contact portion Vc is located at the bottom of the recess 20d on the back surface 20b side of the insulating substrate 20. In the anisotropically conductive member 10, the arithmetic mean distance in the thickness direction Dt between the multiple contact portions Vc and the multiple vertices Pc is 2 nm to 200 nm, preferably 2 nm to 150 nm, more preferably 20 nm to 100 nm, and even more preferably 20 nm to 60 nm.
[0017] In the anisotropically conductive member 10, the surface 20a of the insulating base material 20 from which the protrusions 22a protrude is configured such that the arithmetic mean distance δ between the contacts Vc and the apexes Pc in the thickness direction Dt is 2 nm to 200 nm. When a force acts on the protrusions 22a in a direction parallel to the thickness direction Dt, the protrusions 22a are allowed to bend in the direction x more than when the surface 20a of the insulating base material 20 is a flat surface in which the arithmetic mean distance is less than 2 nm. That is, in the recess 20d, the side surface 22c of the protrusions 22a is allowed to displace in the direction x more than when the surface is flat. This suppresses buckling of the protrusions 22a, so that sufficient bonding strength can be obtained with respect to the connection object, and sufficient conductivity with the connection object can be ensured. Furthermore, there is no contact with adjacent protrusions, and the occurrence of short circuits is also suppressed. Furthermore, when a force acts on the protrusion 22a in a direction parallel to the thickness direction Dt, the protrusion 22a is allowed to deform so that its diameter increases in the direction x, compared to when the surface 20a of the insulating substrate 20 is a flat surface. In this case, the diameter of the protrusion 22a is allowed to increase in the direction x within the recess 20d. Therefore, buckling of the protrusion 22a is suppressed. Even in this case, sufficient bonding strength to the connection object can be obtained, sufficient conductivity with the connection object can be secured, and further, there is no contact with adjacent protrusions, and the occurrence of a short circuit is suppressed.
[0018] When the arithmetic mean distance δ is less than 2 nm, when a force acts on the protrusion 22a in a direction parallel to the thickness direction Dt, the amount of displacement of the protrusion 22a in the direction x is small, and the protrusion 22a buckles. Therefore, sufficient bonding strength to the connection object cannot be obtained. When the protrusion 22a buckles, it may come into contact with an adjacent protrusion, and sufficient conductivity with the connection object cannot be ensured. When the arithmetic mean distance δ exceeds 200 nm, the end on the insulating substrate 20 side becomes closer to the center in the thickness direction Dt of the insulating substrate 20, the recess 20d becomes deeper, and the protrusion 22a becomes substantially longer. Therefore, the protrusion is likely to buckle. When a force acts on the protrusion 22a in a direction parallel to the thickness direction Dt, the protrusion buckles and comes into contact with the adjacent protrusion, and sufficient conductivity with the connection target cannot be ensured.
[0019] The above-mentioned arithmetic mean distance δ can be calculated, for example, as follows. First, the anisotropically conductive member 10 is cut using a focused ion beam (FIB) to expose a cross section of the insulating base material 20 in the thickness direction Dt. A cross section of the insulating base material 20 in the thickness direction Dt is photographed with a field emission scanning electron microscope (FE-SEM) at a magnification of 150k. In the captured image, a reference point Pb is set at an arbitrary position on the back surface 20b opposite to the front surface 20a of the insulating substrate 20. A reference line Ls is set that passes through the reference point Pb and is parallel to the direction x. In the captured image, from among the points corresponding to the apexes Pc, 10 apexes Pc are selected in ascending order of their distance from the reference line Ls, and from among the points corresponding to the contact portions Vc, 10 contact portions Vc are selected in descending order of their distance from the reference line Ls. In the captured image, the distance from the reference line Ls to each of the points corresponding to the selected 10 apexes Pc is calculated. The average of the 10 distances between the points corresponding to the 10 apexes Pc and the reference line Ls is calculated using the least squares method. The average value calculated using the least squares method is displayed as a point on the captured image. A line Lc parallel to the direction x passing through the point indicating the average value of the apexes Pc is calculated. The plane including this parallel line Lc is the average plane of the surface 20a of the insulating substrate 20. The average plane of the surface 20a of the insulating substrate 20 is the reference for the length of the protrusion 22a. In the captured image, the distance from the reference line Ls is calculated for each of the points corresponding to the 10 selected contact areas Vc. The average of the 10 distances between the reference line Ls and the points corresponding to the 10 contact areas Vc is calculated using the least squares method. The average value calculated using the least squares method is displayed as a point on the captured image. A line Lb parallel to the direction x that passes through the point indicating the average value of the contact areas Vc is calculated. The plane including this parallel line Lb is the average plane of the contact areas Vc. The above-mentioned arithmetic mean distance δ is the absolute value of the difference between the average value of the apex Pc calculated using the least squares method and the average value of the contact Vc calculated using the least squares method. That is, the arithmetic mean distance δ is the distance between the parallel line Lc and the parallel line Lb in the thickness direction Dt. Therefore, the arithmetic mean distance δ is obtained by calculating the distance between the parallel line Lc and the parallel line Lb in the thickness direction Dt. Although not shown in detail, the rear surface 20b of the insulating substrate 20 has the same configuration as the front surface 20a of the insulating substrate 20 shown in Fig. 3. The arithmetic mean distance δ of the rear surface 20b of the insulating substrate 20 is also calculated in the same manner as the front surface 20a of the insulating substrate 20 described above.
[0020] [First example of a zygote] Fig. 4 is a schematic cross-sectional view showing a first example of a bonded body according to an embodiment of the present invention, and Fig. 5 is a schematic cross-sectional view showing an enlarged portion of the first example of the bonded body according to an embodiment of the present invention. In addition, in Figs. 4 and 5, the same components as those in the anisotropically conductive member 10 shown in Figs. 1 to 3 are denoted by the same reference numerals, and detailed description thereof will be omitted. 4 is obtained by bonding an anisotropically conductive member 10 to a semiconductor element 30 and a semiconductor element 31 as bonded members. The bonded members are the connection targets. In the bonded body 12, a resin 49 is filled between the anisotropically conductive member 10 and the bonded members. In the semiconductor element 30, for example, three electrodes 34 and an insulating layer 36 that prevents conduction between the three electrodes 34 are provided on a surface 32a of an element substrate 32. The three electrodes 34 are at the same height from the surface 32a of the element substrate 32. In addition, in the semiconductor element 31, for example, on a surface 37a of the element substrate 37, three electrodes 38 and an insulating layer 39 that prevents conduction between the three electrodes 38 are provided. The three electrodes 38 are at the same height from the surface 37a of the element substrate 37. The electrode 34 and the electrode 38 are joined to the conductive path 22 of the anisotropically conductive member 10. For example, as shown in FIG. 5, the electrode 34 is joined in a state in which the surface 34a of the electrode 34 and the protruding portion 22a of the conductive path 22 are in contact with each other. At this time, the surface 34a of the electrode 34 presses the protruding portion 22a of the conductive path 22, and the protruding portion 22a is deformed, but as described above, buckling of the protruding portion 22a is suppressed. Therefore, in the bonded body 12, sufficient bonding strength can be obtained between the semiconductor element 30 and the semiconductor element 31. Furthermore, since buckling of the protruding portion 22a is suppressed, sufficient conductivity with the connection target can be ensured, and further, there is no contact with the adjacent protruding portion, and the occurrence of a short circuit is suppressed.
[0021] The electrodes 34 and 38 are for transmitting and receiving signals with the outside, or for transmitting and receiving voltage or current, and are made of, for example, copper or solder. An electrode made of solder is also called a solder bump. The insulating layer 39 is not particularly limited in configuration as long as it can prevent conduction between electrodes, and can be made of a known insulating layer used in semiconductor elements. The insulating layer 39 is made of, for example, a silicon oxide film (SiO2), a silicon nitride film (Si3N4), a PSG (Phospho Silicate Glass) film, a BPSG (Boron Phospho Silicate Glass) film, or a SOG (Spin On Glass) film.
[0022] The resin layer 33 is formed, for example, by the resin layer 24 of the anisotropically conductive member 10. In this case, the anisotropically conductive member 10 having the resin layer 24 is used for bonding. In addition, the resin layer 33 can also be formed by a resin layer (not shown) provided on the surface 34a of the electrode 34 of the semiconductor element 30 and a resin layer (not shown) provided on the surface 38a of the electrode 38 of the semiconductor element 31. In addition, after joining the conductive path 22 of the anisotropic conductive member 10 to the electrodes 34, 38, a resin agent can be supplied between the conductive path 22 and the electrode 34 and between the conductive path 22 and the electrode 38 to form the resin layer 33.
[0023] (First Example of Manufacturing Method of Bonded Body) The bonded body 12 shown in FIG. 4 is bonded, for example, as shown in FIG. FIG. 6 is a schematic cross-sectional view showing a first example of a method for producing a bonded body according to an embodiment of the present invention. In FIG. 6, the same components as those in the bonded body 12 shown in FIGS. 4 and 5 are denoted by the same reference numerals, and detailed description thereof will be omitted. 6, the semiconductor element 30 and the semiconductor element 31 are arranged with the anisotropically conductive member 10 sandwiched therebetween. At this time, alignment is performed, for example, using alignment marks (not shown) provided on the semiconductor elements 30 and 31 and the anisotropically conductive member 10, respectively. In addition, alignment using an alignment mark is not particularly limited as long as it is possible to obtain an image or reflected image of the alignment mark and determine position information of the alignment mark, and any known alignment method can be used as appropriate. As shown in FIG. 6, a resin layer 24 is provided on the anisotropically conductive member 10, and the resin layer 24 forms the resin layer 33 of the bonded body 12 shown in FIG.
[0024] Next, the semiconductor element 30 is bonded to the anisotropically conductive member 10, and the semiconductor element 31 is bonded to the anisotropically conductive member 10. In this manner, the bonded body 12 shown in FIG. 4 can be manufactured. The bonding process is to bond the semiconductor element 30 and the anisotropically conductive member 10, and the semiconductor element 31 and the anisotropically conductive member 10. In the bonding process, for example, bonding may be performed under predetermined conditions in a provisionally bonded state, but the provisional bonding may be omitted. The bonding in the bonding process is also called a main bonding.
[0025] The temporary bonding means that the semiconductor elements 30 and 31 and the anisotropically conductive member 10 are fixed in an aligned state. The temperature conditions in the temporary bonding process are not particularly limited, but are preferably 0°C to 300°C, more preferably 10°C to 200°C, and particularly preferably room temperature (23°C) to 100°C. Similarly, the pressure conditions in the temporary bonding process are not particularly limited, but are preferably 10 MPa or less, more preferably 5 MPa or less, and particularly preferably 1 MPa or less.
[0026] The temperature conditions for the main bonding are not particularly limited, but it is preferable that the temperature be higher than the temperature for the temporary bonding, specifically, 120°C to 350°C is more preferable, and 200°C to 300°C is particularly preferable. The pressure conditions in the main bonding are not particularly limited, but are preferably 30 MPa or less, and more preferably 0.1 MPa to 20 MPa. The time for the main bonding is not particularly limited, but is preferably from 1 second to 60 minutes, and more preferably from 5 seconds to 10 minutes. By carrying out this bonding under the above conditions, the protrusion 22a of the conductive path 22 is bonded to the surface 34a of the electrode 34, and the protrusion 22b of the conductive path 22 is bonded to the surface 38a of the electrode 38. At this time, as described above, buckling of both the protrusions 22a and 22b of the conductive path 22 is suppressed, and for example, the protrusions 22a, 22b are suppressed from falling over and coming into contact with the adjacent protrusions 22a, 22b. This ensures sufficient bonding strength to the connection objects, ensures sufficient conductivity with the connection objects, and also suppresses the occurrence of short circuits.
[0027] [Second example of a zygote] FIG. 7 is a schematic cross-sectional view showing an enlarged portion of a second example of a bonded body according to an embodiment of the present invention. In FIG. 7, the same components as those in the bonded body 12 shown in FIGS. 4 and 5 are denoted by the same reference numerals, and detailed description thereof will be omitted. The bonded body 13 shown in Fig. 7 differs from the bonded body 12 shown in Fig. 4 and Fig. 5 in that the semiconductor element 30 has electrodes 35 with different heights, but otherwise has the same configuration as the bonded body 12 shown in Fig. 4 and Fig. 5. The electrode 35 is taller than the electrode 34. In the bonded body 13, the electrode 34 and the tall electrode 35 are bonded to the anisotropically conductive member 10. In the bonded body 13, the electrode 35 is closer to the anisotropically conductive member 10 than the electrode 34, and deforms the protruding portion 22a of the conductive path 22 more. Even in this case, the buckling of the protruding portion 22a is suppressed as described above. Even in this configuration in which the semiconductor element 30 has a relatively tall electrode 35, sufficient bonding strength can be obtained between the semiconductor element 30 and the semiconductor element 31. Furthermore, since the buckling of the protruding portion 22a is suppressed, sufficient conductivity is ensured and the occurrence of a short circuit is also suppressed.
[0028] In the bonded bodies 12 and 13, the bonded members have a bonding surface on which a plurality of metal layers are provided, and it is preferable that the area of the bonding surface is larger than the area of the surface from which the protruding portion of the anisotropic conductive member protrudes. Here, the above-mentioned semiconductor elements 30 and 31 have a plurality of electrodes provided on the surface of an element substrate, and the surface of the element substrate corresponds to a bonding surface. The surface area of the element substrate is preferably larger than the surface area of the front surface 20a and the back surface 20b of the insulating base material 20 from which the protruding parts 22a and 22b of the anisotropically conductive member 10 protrude.
[0029] The configuration of the anisotropically conductive member will be described in more detail below.
[0030] (Insulating substrate) The insulating substrate 20 has electrical insulation properties and keeps a plurality of conductive paths 22, which are made of a conductive material, electrically insulated from one another. The insulating substrate 20 has a plurality of pores 21 in which the conductive paths 22 are formed. The composition of the insulating substrate will be described later. The length of the insulating substrate 20 in the thickness direction Dt, i.e., the thickness ht of the insulating substrate 20, is preferably in the range of 1 to 1000 μm, more preferably in the range of 5 to 500 μm, even more preferably in the range of 10 to 300 μm, and particularly preferably 10 μm or more and 30 μm or less. When the thickness of the insulating substrate 20 is in this range, the insulating substrate 20 becomes easy to handle.
[0031] The thickness of the insulating base material is determined by measuring the above-mentioned line Lc on both the front surface 20a side and the back surface 20b side of the insulating base material 20. The distance in the thickness direction Dt between the line Lc on the front surface 20a side and the line Lc on the back surface 20b side is defined as the thickness of the insulating base material.
[0032] The insulating substrate 20 is made of, for example, an inorganic material and has an electrical resistivity (10 14 There are no particular limitations as long as the material has a resistivity of about Ω·cm. Note that "made of inorganic materials" is a definition to distinguish it from the polymeric material that makes up the resin layer described below, and is not a definition that is limited to insulating base materials made up of inorganic materials only, but a definition that has inorganic materials as the main component (50 mass % or more).
[0033] Examples of insulating substrates include metal oxide substrates, metal nitride substrates, glass substrates, ceramic substrates such as silicon carbide and silicon nitride, carbon substrates such as diamond-like carbon, polyimide substrates, composite materials thereof, etc. In addition to the above, the insulating substrate may be, for example, a substrate in which a film is formed on an organic material having a through hole with an inorganic material containing 50 mass % or more of a ceramic material or a carbon material.
[0034] The insulating substrate has through holes formed therein that have micropores having a desired average opening diameter. The insulating substrate is preferably a metal oxide substrate, and more preferably an anodized film of a valve metal, because such a substrate is easy to form conductive paths in. Here, specific examples of valve metals include aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Among these, anodized aluminum film (base material) is preferable because it has good dimensional stability and is relatively inexpensive. For this reason, it is preferable to use an aluminum substrate to form anodized film, which is an insulating base material, and manufacture an anisotropic conductive member. The thickness of the anodized film is the thickness of the insulating base material 20 described above.
[0035] <Aluminum substrate> The aluminum substrate for forming an anodized film, which is an insulating base material, is not particularly limited, and specific examples thereof include a pure aluminum plate; an alloy plate containing aluminum as the main component and trace amounts of other elements; a substrate in which high-purity aluminum is vapor-deposited onto low-purity aluminum (e.g., recycled materials); a substrate in which the surface of a silicon wafer, quartz, glass, or the like is coated with high-purity aluminum by a method such as vapor deposition or sputtering; a resin substrate laminated with aluminum; and the like.
[0036] In the aluminum substrate, the surface on which the anodized film is provided by the anodizing process has an aluminum purity of preferably 99.5% by mass or more, more preferably 99.9% by mass or more, and even more preferably 99.99% by mass or more. When the aluminum purity is within the above range, the through-hole arrangement has sufficient regularity. The micropores become fine pores. The aluminum substrate is not particularly limited as long as it is capable of forming an anodized film, and for example, JIS (Japanese Industrial Standards) 1050 material is used.
[0037] In addition, it is preferable that the surface of one side of the aluminum substrate to be subjected to the anodizing process is previously subjected to a heat treatment, a degreasing treatment and a mirror finish treatment. Here, the heat treatment, degreasing treatment and mirror finish treatment may be the same as those described in paragraphs
[0044] to
[0054] of JP2008-270158A. The mirror finish treatment prior to the anodizing treatment is, for example, electrolytic polishing, and for the electrolytic polishing, for example, an electrolytic polishing solution containing phosphoric acid is used.
[0038] <Average pore diameter> The average diameter of pores 21 is preferably 1 μm or less, more preferably 5 to 500 nm, even more preferably 20 to 400 nm, even more preferably 40 to 200 nm, and most preferably 50 to 100 nm. When the average diameter d of pores 21 is 1 μm or less and within the above range, conductive paths 22 having the above average diameter can be obtained. The average diameter of the pores 21 can be obtained, for example, as follows. First, a scanning electron microscope (SEM) is used to photograph the surface of the insulating substrate 20 from directly above at a magnification of 100 to 10,000 times to obtain a photographed image. In the photographed image, at least 20 pores that are connected in a ring shape are extracted, and their diameters are measured to determine the opening diameter. The average of these opening diameters is calculated as the average diameter of the pores. The magnification can be appropriately selected from the above range so that a captured image can be obtained that can extract 20 or more pores. The aperture diameter is measured by measuring the maximum value of the distance between the ends of the pore portion. That is, since the shape of the opening of the pore is not limited to a substantially circular shape, when the shape of the opening is non-circular, the maximum value of the distance between the ends of the pore portion is taken as the aperture diameter. Therefore, for example, even in the case of a pore having a shape in which two or more pores are integrated, this is regarded as one pore, and the maximum value of the distance between the ends of the pore portion is taken as the aperture diameter.
[0039] <Conduction Path> As described above, the plurality of conductive paths 22 are provided in the insulating base material 20, for example, an anodized film, in a state in which they are electrically insulated from each other. Each of the plurality of conductive paths 22 is a columnar conductor having electrical conductivity and is made of a conductive material. The conductive material is not particularly limited, and may be, for example, a metal. Specific examples of metals include gold (Au), silver (Ag), copper (Cu), aluminum (Al), magnesium (Mg), nickel (Ni), zinc (Zn), and cobalt (Co). As the conductive material, from the viewpoint of electrical conductivity and formation by plating, copper (Cu), gold (Au), aluminum (Al), nickel (Ni), and cobalt (Co) are preferred, copper (Cu), gold (Au), and aluminum (Al) are more preferred, and copper (Cu) is even more preferred. Metals have superior ductility and other properties compared to oxide conductors, and are therefore more easily deformed, even when compressed during bonding. Therefore, it is preferable to form the conductive paths from a metal.
[0040] The average diameter d of the conductive paths 22 is preferably 1 μm or less, more preferably 5 to 500 nm, even more preferably 20 to 400 nm, even more preferably 40 to 200 nm, and most preferably 50 to 100 nm. The density of the conductive paths 22 is 20,000 pieces / mm 2 More than 2 million particles / mm is preferable. 2 More preferably, it is 10 million particles / mm 2More preferably, it is 50 million particles / mm 2 More preferably, the number is 100 million / mm 2 More preferably, it is equal to or greater than this. Furthermore, the center-to-center distance p between adjacent conductive paths 22 is preferably 20 nm to 500 nm, more preferably 40 nm to 200 nm, and even more preferably 50 nm to 140 nm. Regarding the conductive paths 22, the distance w between adjacent protrusions (see FIG. 1) is 20 nm to 200 nm, and preferably 40 nm to 100 nm. When the distance between adjacent protrusions is within the above range, the distance between the conductive paths 22 can be maintained even on the front surface 20a or back surface 20b of the insulating substrate 20 of the conductive paths 22. This prevents short circuits in the conductive paths 22 during bonding, and increases reliability during bonding.
[0041] The average diameter of the conductive paths can be obtained, for example, as follows. First, a scanning electron microscope is used to photograph the surface of the insulating substrate from directly above at a magnification of 100 to 10,000 times to obtain a photographed image. In the photographed image, at least 20 conductive paths that are connected in a ring shape are extracted, and their diameters are measured to determine the opening diameter. The average of these opening diameters is calculated as the average diameter of the conductive paths. The magnification can be appropriately selected from the above range so that a captured image can be obtained that can extract 20 or more conductive paths. When the opening has a non-circular shape, the maximum value of the distance between the ends of the conductive path portion is taken as the opening diameter. Therefore, even when a conductive path has a shape in which two or more conductive paths are integrated, this is regarded as one conductive path, and the maximum value of the distance between the ends of the conductive path portion is taken as the opening diameter. The average diameter d of the conductive paths 22 is the same as the average diameter of the protrusions. When the conductive paths 22 on the front surface 20a of the insulating substrate 20 are not circular, the average diameter of the conductive paths 22 on the front surface 20a of the insulating substrate 20 is taken as the average diameter of the circle-equivalent diameter. When the conductive paths 22 on the back surface 20b of the insulating substrate 20 are not circular, the average diameter of the conductive paths 22 on the back surface 20b of the insulating substrate 20 is taken as the average diameter of the circle-equivalent diameter. Furthermore, the average diameter d of the conductive paths 22 on the front surface 20a side of the insulating substrate 20 can be measured from a front surface image of the front surface 20a of the insulating substrate 20 obtained by a scanning electron microscope. The average diameter d of the conductive paths 22 on the back surface 20b of the insulating substrate 20 can be measured from a back surface image of the back surface 20b of the insulating substrate 20 obtained by a scanning electron microscope.
[0042] When using the front and back images as described above, if protruding parts make it difficult to measure the average diameter, the protruding parts are removed by dissolving or the like. This causes pores to appear. The opening diameters of a plurality of pores in the front image in this state are measured, and the average opening diameter of the pores on the front side can be used instead of the average diameter on the front side. Similarly, the opening diameters of a plurality of pores in the back image in this state can be measured, and the average opening diameter of the pores on the back side can be used instead of the average diameter on the back side. The average opening diameter of the pores can be measured, for example, as follows. First, 20 pores are selected from the surface image, and the diameters of the pores at the openings are measured for the 20 pores. The average value of the diameters of the pores is calculated, and this average value is regarded as the average opening diameter of the pores on the surface side. In addition, 20 pores are selected from the backside image, and the diameters of the pores are measured for the 20 pores. The average of the diameters of the pores is calculated, and this average is regarded as the average opening diameter of the pores on the backside.
[0043] The center-to-center distance p of adjacent conductive paths 22 is determined by further identifying the center positions (not shown) of the identified conductive paths in the photographed image of insulating substrate 20 obtained as described above. The distance between the center positions of adjacent conductive paths was determined at 10 locations. The average value was taken as the center-to-center distance p of adjacent conductive paths 22. The center positions are the center positions of the areas corresponding to conductive paths 22 in the photographed image described above. A known image analysis method is used to calculate the center positions of the areas in the photographed image.
[0044] <<Protrusion>> The protrusion is a part of the conductive path and is columnar. The protrusion is preferably cylindrical in shape because this increases the contact area with the workpiece. The length h of the protrusion 22a in the thickness direction Dt of the insulating base material 20 and the length h of the protrusion 22b in the thickness direction Dt of the insulating base material 20 are preferably 2 nm to 6000 nm, more preferably 5 nm to 3000 nm. If the length h is 10 nm to 1000 nm, good bonding to the bonded member can be achieved. The length h of the protrusion 22a and the length h of the protrusion 22b are determined based on the average plane of the surface 20a of the insulating base material 20 described above. If the length h of the above-mentioned protrusions 22a and 22b in the thickness direction Dt of the insulating base material 20 is 2 nm to 6000 nm, the bump height distribution tracking ability of the bumps on the bonded object side is good, and height accuracy of the bump surface on the bonded object side is not required.
[0045] For the length h of the protrusion 22a and the length h of the protrusion 22b, a field emission scanning electron microscope (FE-SEM) is used to obtain an image at a magnification of 100,000 times of a cross section in the thickness direction Dt of the insulating base material 20. In the image, the line Lc on the front side of the insulating base material and the line Lc on the back side of the insulating base material are obtained as described above. Next, ten protrusions 22a are selected in the captured image. Points corresponding to the tops of the selected ten protrusions 22a are identified. The distance between the point corresponding to the top of the identified protrusion 22a and the line Lc on the front surface side of the insulating substrate in the thickness direction Dt of the insulating substrate 20 is calculated for each of the ten protrusions 22a. The average value of the above-mentioned distances between the points corresponding to the tops of the ten protrusions 22a is calculated. This average value is set as the length h of the protrusion 22a. Further, ten protrusions 22b are selected in the captured image. Points corresponding to the tops of the selected ten protrusions 22b are identified. The distance between the point corresponding to the top of the identified protrusion 22b and the line Lc on the rear surface side of the insulating substrate in the thickness direction Dt of the insulating substrate 20 is calculated for each of the ten protrusions 22b. The average value of the above-mentioned distances between the points corresponding to the tops of the ten protrusions 22b is calculated. This average value is set as the length h of the protrusion 22b. When the diameter of the protrusion is d and the length of the protrusion in the thickness direction of the insulating base material is h, the aspect ratio d / h is preferably 0.1 to 20. When the aspect ratio d / h is 0.1 to 20, stable production is possible and the bonding strength is excellent.
[0046] [Resin Layer] As described above, the resin layer covers at least one of the front and back surfaces of the insulating substrate, and protects the insulating substrate and the conductive paths. For example, if the conductive paths have protruding portions, the resin layer buries the protruding portions. That is, the resin layer covers the ends of the conductive paths protruding from the insulating substrate, and protects the protruding portions. In order to exert the above-mentioned functions, the resin layer preferably exhibits fluidity in a temperature range of, for example, 50° C. to 200° C. and hardens at temperatures of 200° C. or higher. The resin layer is, for example, a thermoplastic layer made of a thermoplastic resin or the like, and the resin layer will be described in detail later. The average thickness hm of the resin layer 24 is preferably 10 μm or less, more preferably 5 μm or less, and further preferably 1 μm or less. If the average thickness hm of the resin layer 24 is 10 μm or less as described above, the resin layer 24 can sufficiently exhibit the effect of protecting the protruding parts of the conductive paths 22 and filling the periphery of the electrodes when bonding to a connection target such as a semiconductor device. The average thickness hm of the resin layer 24 is the average distance from the front surface 20a of the insulating substrate 20, or the average distance from the back surface 20b of the insulating substrate 20. The average thickness hm of the resin layer 24 described above is determined by cutting the resin layer in the thickness direction Dt of the anisotropically conductive member 10, and obtaining a photographed image of the cut cross section using a scanning electron microscope. In the photographed image, the line Lc on the front surface side of the insulating substrate and the line Lc on the back surface side of the insulating substrate are obtained as described above. Next, ten locations corresponding to the surface of the resin layer are selected in the captured image. The distance between the selected location and the line Lc on the surface side of the insulating base material is calculated for each of the ten locations. The average value of the distances at the ten locations is calculated. This average value is set as the average thickness hm of the resin layer 24 on the surface 20a side of the insulating base material 20. Similarly, ten locations corresponding to the surface of the resin layer are selected from the captured image of the resin layer on the back surface 20b of the insulating substrate 20. The distance between the selected location and the line Lc on the back surface of the insulating substrate is calculated for each of the ten locations. The average value of the distances at the ten locations is calculated. This average value is regarded as the average thickness hm of the resin layer 24 on the back surface 20b of the insulating substrate 20.
[0047] The resin layer may have the following composition: The composition of the resin layer will be described below: For example, the resin layer contains a polymer material and may contain an antioxidant material. Specific examples of the resin material constituting the resin layer include thermoplastic resins such as ethylene copolymers, polyamide resins, polyester resins, polyurethane resins, polyolefin resins, acrylic resins, acrylonitrile resins, and cellulose resins. Polyacrylonitrile can also be used as the resin material constituting the resin layer. Examples of the resin material constituting the resin layer include epoxy resins, phenolic resins, polyimide resins, melamine resins, and isocyanate resins. Among these, polyimide resins and / or epoxy resins are preferably used because they have improved insulation reliability and excellent chemical resistance. As the resin layer, in addition to those described above, for example, a resin layer containing a main composition containing an acrylic polymer, an acrylic monomer, and a maleimide compound described in WO 2022 / 163260 can be used.
[0048] ((Anisotropically conductive material to be joined)) When the anisotropic conductive member is used as an electronic connection member, the member to be connected is, for example, a semiconductor element, an electrode, or an element region. Examples of the member having an electrode include a semiconductor element that exerts a specific function by itself, but also includes a plurality of elements that exert a specific function together. Furthermore, it also includes elements that only transmit electrical signals such as wiring members, and printed wiring boards are also included in the members having electrodes. The element region is a region in which various element configuration circuits and the like for functioning as electronic elements are formed. The element region is, for example, a region in which a memory circuit such as a flash memory, a logic circuit such as a microprocessor and an FPGA (field-programmable gate array), a communication module such as a wireless tag, and wiring are formed. In addition to the above, MEMS (Micro Electro Mechanical Systems) may be formed in the element region. Examples of MEMS include sensors, actuators, and antennas. Examples of sensors include various sensors such as acceleration, sound, and light sensors. The optical sensor is not particularly limited as long as it can detect light, and for example, a CCD (Charge Coupled Device) image sensor or a CMOS (Complementary Metal Oxide Semiconductor) image sensor is used. As described above, the element region has an element configuration circuit and the like formed therein, and electrodes (not shown) are provided to electrically connect the semiconductor chip to the outside. The element region has an electrode region in which electrodes are formed. The electrodes in the element region are, for example, Cu posts. The electrode region is basically a region that includes all the formed electrodes. However, if the electrodes are provided discretely, the region in which each electrode is provided is also called the electrode region. The form of the structure may be an individual piece such as a semiconductor chip, a semiconductor wafer, or a wiring layer. In addition, the structure is joined to a connection object, but the connection object is not particularly limited to the above-mentioned semiconductor elements, etc., and examples of the connection object include semiconductor elements in a wafer state, semiconductor elements in a chip state, printed wiring boards, and heat sinks, etc.
[0049] ((Semiconductor element)) In addition to the above, the semiconductor element may be, for example, a logic LSI (Large Scale Integration) (e.g., ASIC (Application Specific Integrated Circuit), FPGA (Field Programmable Gate Array), ASSP (Application Specific Standard Product), etc.), a microprocessor (e.g., CPU (Central Processing Unit), GPU (Graphics Processing Unit), etc.), a memory (e.g., DRAM (Dynamic Random Access Memory), HMC (Hybrid Memory Cube), MRAM (Magnetic RAM), PCM (Phase-Change Memory), ReRAM (Resistive RAM), FeRAM (Ferroelectric RAM), flash memory (NAND (Not AND) flash), etc.), an LED (Light Emitting Diode) (e.g., micro flash of a mobile terminal, an in-vehicle device, a projector light source, an LCD backlight, general lighting, etc.), a power device, an analog IC (Integrated Circuit), (e.g., DC (Direct Current (DC)-DC (Direct Current) converters, Insulated Gate Bipolar Transistors (IGBTs), etc.), MEMS (Micro Electro Mechanical Systems) (e.g., acceleration sensors, pressure sensors, vibrators, gyro sensors, etc.), wireless (e.g., GPS (Global Positioning System), FM (Frequency Modulation), NFC (Nearfield communication), RFEM (RF Expansion Module), MMIC (Monolithic Microwave Integrated Circuit), WLAN (Wireless Local Area Network), etc.), discrete elements, BSI (Back Side Illumination), CIS (Contact ImageSensors, camera modules, CMOS (Complementary Metal Oxide Semiconductors), passive devices, SAW (Surface Acoustic Wave) filters, RF (Radio Frequency) filters, RFIPDs (Radio Frequency Integrated Passive Devices), and BB (Broadband). The semiconductor element is, for example, a self-contained device that performs a specific function such as a circuit or a sensor by itself. The semiconductor element may have an interposer function. For example, a logic chip having a logic circuit and a plurality of devices such as a memory chip can be stacked on a device having an interposer function. In this case, the devices can be joined even if the electrode sizes are different for each device.
[0050] (One example of a method for producing an anisotropic conductive member) Next, a method for producing an anisotropically conductive member will be described. Figures 8 to 14 are schematic cross-sectional views showing an example of a method for producing an anisotropically conductive member according to an embodiment of the present invention in the order of steps. In Figures 8 to 14, the same components as those in the anisotropically conductive member 10 shown in Figures 1 to 3 are given the same reference numerals, and detailed descriptions thereof will be omitted. In one example of the method for producing an anisotropically conductive member, an anisotropically conductive member 10 shown in Fig. 1 in which the insulating base material 20 is made of an anodized aluminum film will be described. In order to form the anodized aluminum film, an aluminum substrate is used. Therefore, in one example of the method for producing an anisotropically conductive member, an aluminum substrate 40 is first prepared as shown in Fig. 8. The size and thickness of the aluminum substrate 40 are appropriately determined depending on the thickness of the insulating base material 20 (see FIG. 1) of the anisotropic conductive member 10 (see FIG. 1) to be finally obtained, the processing device, etc. The aluminum substrate 40 is, for example, a plate material having a circular outer shape. Note that the aluminum substrate is not limited to an aluminum substrate, and any metal substrate capable of forming an electrically insulating insulating film can be used. A valve metal capable of forming an anodized film by anodization can be used.
[0051] Next, one surface 40a (see FIG. 8) of the aluminum substrate 40 is anodized. As a result, one surface 40a (see FIG. 8) of the aluminum substrate 40 is anodized to form an anodized film 44 having a plurality of pores 21 extending in the thickness direction Dt of the aluminum substrate 40, as shown in FIG. The anodized film 44 is the insulating base material 20 (see FIG. 1) described above. As shown in FIG. 9, a barrier layer 43 exists at the bottom of each pore 21. The above-mentioned anodizing process is called an anodizing process. As described above, the anodized film 44 having the multiple pores 21 has a barrier layer 43 at the bottom of each pore 21, but the barrier layer 43 is removed. As a result, an anodized film 44 having the multiple pores 21 and no barrier layer 43 (see FIG. 10) is obtained. The step of removing the barrier layer 43 is referred to as a barrier layer removal step.
[0052] In the barrier layer removal step, an alkaline aqueous solution containing ions of a metal M1 having a higher hydrogen overvoltage than aluminum is used to remove the barrier layer 43 of the anodic oxide film 44, and at the same time, a metal layer 45a (see FIG. 10) made of a metal (metal M1) is formed on a surface 42d (see FIG. 10) of a bottom 42c (see FIG. 10) of the pore 21. As a result, the aluminum substrate 40 exposed in the pore 21 is covered with the metal layer 45a. As a result, when the pore 21 is filled with metal by plating, plating is facilitated, and the pore is prevented from being insufficiently filled with metal, and the pore 21 is prevented from being left unfilled with metal, thereby preventing poor formation of the conductive path 22 (see FIG. 1). The alkaline aqueous solution containing the metal M1 ions may further contain an aluminum ion-containing compound (sodium aluminate, aluminum hydroxide, aluminum oxide, etc.). The content of the aluminum ion-containing compound is preferably 0.1 to 20 g / L, more preferably 0.3 to 12 g / L, and even more preferably 0.5 to 6 g / L, calculated as the amount of aluminum ions.
[0053] Next, plating is performed from the surface 44a of the anodic oxide film 44 having a plurality of pores 21 extending in the thickness direction Dt. In this case, the metal layer 45a can be used as an electrode for electrolytic plating. A metal 45b is used for plating, and plating proceeds starting from the metal layer 45a formed on the surface 42d (see FIG. 10) of the bottom 42c (see FIG. 10) of the pore 21. As a result, as shown in FIG. 11, the metal 45b is filled inside the pore 21 of the anodic oxide film 44 as a conductive material constituting the conductive path 22. The conductive path 22 is formed by filling the inside of the pore 21 with the metal 45b. The metal layer 45a and the metal 45b are collectively referred to as the filled metal 45. The process of filling the pores 21 of the anodic oxide film 44 with metal 45b to form the conductive paths 22 is referred to as the metal filling process. As described above, the conductive paths 22 are made of a conductive material, and are not limited to being filled with metal. Electrolytic plating is used in the metal filling process, which will be described in detail later. Note that the surface 44a of the anodic oxide film 44 corresponds to one surface of the insulating base material 20. The process of filling the pores 21 of the anodic oxide film 44 with a conductive material, including metal and non-metal materials, to form the conductive paths 22 is simply referred to as the filling process.
[0054] After the metal filling step, a polishing step is carried out to polish and smooth the surface 44a of the anodic oxide film 44 shown in Fig. 11. For the polishing, for example, a chemical mechanical polishing (CMP) process is used. Next, after the polishing step, as shown in Fig. 12, surface 20a of anodized film 44 on the side where aluminum substrate 40 is not provided is partially removed in thickness direction Dt, and metal 45 filled in the metal filling step is made to protrude from surface 44a of anodized film 44. That is, conductive path 22 is made to protrude from surface 44a of anodized film 44. Thus, protruding portion 22a is obtained. The step of making conductive path 22 protrude from surface 44a of anodized film 44 is called a surface protruding step. In the surface protruding step, the surface 44a of the anodized film 44 is dissolved using, for example, a solution that dissolves the anodized film 44 without dissolving the metal that constitutes the conductive paths 22. At this time, a spray etching method is used in which the dissolving solution is made into droplets and sprayed onto the surface 44a of the anodized film 44. As a result, the surface 20a of the insulating base material 20 shown in FIG. 3 is obtained.
[0055] After the surface protruding step, the aluminum substrate 40 is removed as shown in Fig. 13. The step of removing the aluminum substrate 40 is called a substrate removing step. In the case of a configuration with only one protruding portion, the state shown in Fig. 13 can be used as the anisotropically conductive member 10. In this case, in the state shown in Fig. 13, a resin layer 24 (see Fig. 1) is formed to cover the entire surface 44a of the anodic oxide film 44 from which the protruding portion 22a protrudes, to provide the anisotropically conductive member 10.
[0056] 14, after the substrate removal step, a polishing step is performed to polish and smooth the surface of the anodic oxide film 44 on the side where the aluminum substrate 40 was provided, i.e., the back surface 44b of the anodic oxide film 44. For example, a CMP process is used for the polishing. Next, after the polishing process of the back surface 44b of the anodic oxide film 44, the back surface 44b of the anodic oxide film 44 is partially removed in the thickness direction Dt as shown in FIG. 14, and the metal 45 filled in the metal filling process, i.e., the conductive path 22, is made to protrude from the back surface 44b of the anodic oxide film 44. In this way, the protruding portion 22b is obtained. The process of making the conductive path 22 protrude from the back surface 44b of the anodic oxide film 44 is called the back surface protruding process. Note that the back surface protruding process does not necessarily have to be performed. If the back surface protruding process is not performed, the above-mentioned protruding portion 22b is not formed. In the back surface protruding step, similarly to the front surface protruding step, the back surface 44b of the anodized film 44 is dissolved using, for example, a solution that dissolves the anodized film 44 without dissolving the metal that constitutes the conductive paths 22. At this time, a spray etching method is used in which the dissolving solution is made into droplets and sprayed onto the back surface 44b of the anodized film 44. As a result, the back surface 20b similar to the front surface 20a of the insulating base material 20 shown in FIG. 3 is obtained.
[0057] The above-mentioned front surface protruding step and back surface protruding step may be both steps, or one of the front surface protruding step and back surface protruding step may be one. The front surface protruding step and back surface protruding step are both "protruding steps", and both the front surface protruding step and back surface protruding step are protruding steps. The protruding step is also called a trimming step. When the protruding step is performed, the thickness of the anodic oxide film 44 after the protruding step is the thickness of the insulating base material.
[0058] Next, as shown in Fig. 14, a resin layer 24 (see Fig. 1) is formed to cover the entire surface 44a of the anodic oxide film 44 from which the protruding portions 22a protrude. Also, a resin layer 24 (see Fig. 1) is formed to cover the entire back surface 44b of the anodic oxide film 44 from which the protruding portions 22b protrude. In this way, the anisotropically conductive member 10 shown in Fig. 1 is manufactured.
[0059] [Anodizing process] Although a conventionally known method can be used for the anodization treatment, it is preferable to use a self-ordering method or a constant voltage treatment from the viewpoint of increasing the regularity of the micropore arrangement and ensuring the anisotropic conductivity of the structure, which results in, for example, a hexagonal arrangement of the pores and conductors. Here, the self-ordering method of the anodizing treatment and the constant voltage treatment can be the same as the treatments described in paragraphs
[0056] to
[0108] and in FIG. 8 of JP-A-2008-270158.
[0060] [Holding process] When manufacturing an anisotropically conductive member, a holding step may be included. The holding step is a step of holding the anisotropically conductive member for a total of 5 minutes or more at a voltage of 95% to 105% of a holding voltage selected from a range of 1 V or more and less than 30% of the voltage in the anodizing step after the anodizing step. In other words, the holding step is a step of performing an electrolytic treatment for a total of 5 minutes or more at a voltage of 95% to 105% of a holding voltage selected from a range of 1 V or more and less than 30% of the voltage in the anodizing step after the anodizing step. Here, the "voltage in anodizing treatment" refers to the voltage applied between the aluminum substrate and the counter electrode. For example, if the electrolysis time in anodizing treatment is 30 minutes, the voltage refers to the average voltage maintained during that 30 minutes.
[0061] From the viewpoint of controlling the sidewall thickness of the anodized film, i.e., the thickness of the barrier layer to an appropriate thickness relative to the depth of the pores, the voltage in the holding step is preferably 5% to 25% of the voltage in the anodizing treatment, and more preferably 5% to 20%.
[0062] Furthermore, in order to further improve the in-plane uniformity, the total holding time in the holding step is preferably 5 minutes or more and 20 minutes or less, more preferably 5 minutes or more and 15 minutes or less, and even more preferably 5 minutes or more and 10 minutes or less. The holding time in the holding step may be a total of 5 minutes or more, but is preferably 5 minutes or more continuously.
[0063] Furthermore, the voltage in the holding step may be set by decreasing continuously or stepwise from the voltage in the anodizing treatment step to the voltage in the holding step. However, in order to further improve the in-plane uniformity, it is preferable to set the voltage to 95% or more and 105% or less of the above-mentioned holding voltage within 1 second after the end of the anodizing treatment step.
[0064] The above-mentioned holding step can also be carried out consecutively with the above-mentioned anodizing step, for example by lowering the electrolytic potential at the end of the above-mentioned anodizing step. In the above-mentioned holding step, the same electrolytic solution and treatment conditions as those in the above-mentioned conventionally known anodizing treatment can be adopted, except for the electrolytic potential. In particular, when the holding step and the anodizing step are carried out successively, it is preferable to carry out the treatment using the same electrolyte.
[0065] In the anodized film having a plurality of pores (micropores), as described above, a barrier layer (not shown) exists at the bottom of the pores, and the method includes a barrier layer removal step for removing this barrier layer.
[0066] [Barrier layer removal process] The barrier layer removal step is a step of removing the barrier layer of the anodized film using, for example, an alkaline aqueous solution containing ions of a metal M1 having a higher hydrogen overvoltage than aluminum. By the above-mentioned barrier layer removal step, the barrier layer is removed, and a conductive layer made of metal M1 is formed at the bottom of the pore. Here, hydrogen overvoltage refers to the voltage required to generate hydrogen, and for example, the hydrogen overvoltage of aluminum (Al) is −1.66 V (Journal of the Chemical Society of Japan, 1982, (8), pp. 1305-1313). Examples of metals M1 with hydrogen overvoltages higher than that of aluminum and their hydrogen overvoltage values are shown below. <Metal M1 and hydrogen (1N H2SO4) overvoltage> ·Platinum (Pt): 0.00V ·Gold (Au): 0.02V ·Silver (Ag): 0.08V Nickel (Ni): 0.21V ·Copper (Cu):0.23V ·Tin (Sn): 0.53V Zinc (Zn): 0.70V
[0067] In the above-mentioned barrier layer removal step, the barrier layer is removed using an alkaline aqueous solution containing ions of metal M1, which has a higher hydrogen overvoltage than aluminum, thereby not only removing the barrier layer 43 but also forming a metal layer 45a of metal M1, which is less likely to generate hydrogen gas than aluminum, on the aluminum substrate 40 exposed at the bottom of the pores 21. As a result, the in-plane uniformity of the metal filling is improved. This is thought to be because the generation of hydrogen gas by the plating solution is suppressed, making it easier to proceed with metal filling by electrolytic plating. In addition, it has been found that the uniformity of metal filling during plating is greatly improved by providing a holding step in the barrier layer removal step, in which a voltage (holding voltage) selected from a range of less than 30% of the voltage in the anodizing step is held for a total of 5 minutes or more, and combining this with the application of an alkaline aqueous solution containing ions of metal M1. For this reason, it is preferable to have a holding step. Although the detailed mechanism is unknown, it is believed that in the barrier layer removal process, an alkaline aqueous solution containing ions of metal M1 is used, which forms a layer of metal M1 at the bottom of the barrier layer, thereby preventing damage to the interface between the aluminum substrate and the anodized film and improving the uniformity of the dissolution of the barrier layer.
[0068] In the barrier layer removal step, metal layer 45a made of a metal (metal M1) is formed at the bottom of pore 21, but the present invention is not limited to this, and only barrier layer 43 is removed to expose aluminum substrate 40 at the bottom of pore 21. In a state where aluminum substrate 40 is exposed, aluminum substrate 40 may be used as an electrode for electrolytic plating.
[0069] The pores 21 can also be formed by widening the diameter of the micropores and removing the barrier layer. In this case, a pore widening process is used to widen the diameter of the micropores. The pore widening process is a process in which the anodized film is dissolved by immersing the anodized film in an acidic or alkaline aqueous solution, thereby widening the pore diameter of the micropores. For the pore widening process, an aqueous solution of an inorganic acid such as sulfuric acid, phosphoric acid, nitric acid, or hydrochloric acid, or a mixture thereof, or an aqueous solution of sodium hydroxide, potassium hydroxide, lithium hydroxide, or the like can be used. The barrier layer at the bottom of the micropores can also be removed by the pore widening treatment. By using an aqueous sodium hydroxide solution in the pore widening treatment, the micropores are enlarged and the barrier layer is removed.
[0070] [Filling process] The filling step is a step of forming a plurality of conductive paths by filling a conductive material into the pores of an anodized film having a plurality of pores extending in the thickness direction, i.e., an insulating base material. The conductive paths are, for example, columnar conductors. When a metal is filled in the filling step, it is called a metal filling step. <Metals used in the filling process> In the filling step, the metal filled as a conductive material into the pores 21 of the anodic oxide film 44 described above in order to form a conductive path has an electrical resistivity of 10 3 It is preferable that the material has a resistivity of Ω·cm or less. Specific examples of the above-mentioned metals include gold (Au), silver (Ag), copper (Cu), aluminum (Al), magnesium (Mg), nickel (Ni), zinc (Zn) and cobalt (Co). From the viewpoints of electrical conductivity and formation by a plating method, the conductive material is preferably copper (Cu), gold (Au), aluminum (Al), nickel (Ni) or cobalt (Co), more preferably copper (Cu) or gold (Au), and even more preferably copper (Cu).
[0071] <Plating method> For the anodic oxide film 44 having the multiple pores 21 extending in the thickness direction Dt, the plating method for filling the inside of the pores 21 with metal may be, for example, electrolytic plating or electroless plating. Here, it is difficult to selectively deposit (grow) a metal in a hole with a high aspect ratio using a conventional electrolytic plating method used for coloring, etc. This is thought to be because the deposited metal is consumed in the hole and the plating does not grow even if electrolysis is performed for a certain period of time or more. Therefore, when filling metal by electrolytic plating, it is necessary to provide a rest period during pulse electrolysis or constant potential electrolysis. The rest period must be 10 seconds or more, and is preferably 30 to 60 seconds. It is also preferable to apply ultrasonic waves to promote stirring of the electrolyte.
[0072] Furthermore, the electrolysis voltage is usually 20 V or less, and preferably 10 V or less, but it is preferable to measure the deposition potential of the target metal in the electrolyte solution to be used in advance and perform constant-potential electrolysis at a potential within +1 V. When performing constant-potential electrolysis, it is preferable to use a device that can also be used with cyclic voltammetry, and potentiostat devices such as those manufactured by Solartron, BAS Corporation, Hokuto Denko Corporation, and IVIUM Corporation can be used.
[0073] (Plating solution) As the plating solution, a conventionally known plating solution can be used. Specifically, when copper is precipitated, an aqueous solution of copper sulfate is generally used, and the concentration of the copper sulfate is preferably 1 to 300 g / L, more preferably 100 to 200 g / L. The precipitation can be promoted by adding hydrochloric acid to the electrolytic solution. In this case, the concentration of hydrochloric acid is preferably 10 to 20 g / L. When gold is to be deposited, it is preferable to use a sulfuric acid solution of gold tetrachloride and to perform plating by AC electrolysis.
[0074] The plating solution preferably contains a surfactant. Any known surfactant can be used. Sodium lauryl sulfate, which is known as a surfactant conventionally added to plating solutions, can also be used as is. Both surfactants with ionic (cationic, anionic, zwitterionic) and nonionic (nonionic) hydrophilic moieties can be used, but cationic surfactants are preferred in order to avoid the generation of bubbles on the surface of the object to be plated. The concentration of surfactant in the plating solution composition is preferably 1 mass % or less. In electroless plating, it takes a long time to completely fill the pores having high aspect ratios with metal, so it is preferable to fill the pores with metal by electrolytic plating.
[0075] [Substrate removal process] The substrate removing step is a step of removing the aluminum substrate after the filling step. The method for removing the aluminum substrate is not particularly limited, and a suitable example is a method of removing the aluminum substrate by dissolving it.
[0076] <Dissolving aluminum substrate> The above-mentioned aluminum substrate is preferably dissolved using a treatment liquid that does not easily dissolve an anodized film but easily dissolves aluminum. The dissolution rate of such a treatment solution for aluminum is preferably 1 μm / min or more, more preferably 3 μm / min or more, and even more preferably 5 μm / min or more.Similarly, the dissolution rate of anodized film is preferably 0.1 nm / min or less, more preferably 0.05 nm / min or less, and even more preferably 0.01 nm / min or less. Specifically, the treatment liquid preferably contains at least one metal compound having a lower ionization tendency than aluminum, and has a pH of 4 or less or 8 or more, more preferably a pH of 3 or less or 9 or more, and even more preferably a pH of 2 or less or 10 or more.
[0077] The treatment liquid for dissolving aluminum is preferably based on an acid or alkaline aqueous solution and contains, for example, compounds of manganese, zinc, chromium, iron, cadmium, cobalt, nickel, tin, lead, antimony, bismuth, copper, mercury, silver, palladium, platinum, and gold (e.g., chloroplatinic acid), their fluorides, and their chlorides. Among these, an acid aqueous solution base is preferred, and it is also preferred to blend a chloride. In particular, a treatment solution in which mercury chloride is blended with an aqueous hydrochloric acid solution (hydrochloric acid / mercury chloride) and a treatment solution in which copper chloride is blended with an aqueous hydrochloric acid solution (hydrochloric acid / copper chloride) are preferred from the viewpoint of treatment latitude. The composition of the treatment liquid for dissolving aluminum is not particularly limited, and for example, a bromine / methanol mixture, a bromine / ethanol mixture, aqua regia, etc. can be used.
[0078] The acid or alkali concentration of the treatment liquid for dissolving aluminum is preferably from 0.01 to 10 mol / L, and more preferably from 0.05 to 5 mol / L. Furthermore, the treatment temperature using the treatment liquid that dissolves aluminum is preferably from -10°C to 80°C, and more preferably from 0°C to 60°C.
[0079] The aluminum substrate is dissolved by contacting the aluminum substrate after the plating step with the treatment solution. The contact method is not particularly limited, and examples thereof include an immersion method and a spray method. Among these, the immersion method is preferred. The contact time is preferably 10 seconds to 5 hours, more preferably 1 minute to 3 hours.
[0080] When forming the anisotropically conductive member, for example, a support substrate may be provided on the anodized film 44. The support substrate preferably has the same outer shape as the anodized film 44. By attaching the support substrate, the anodized film 44 becomes easier to handle when forming the anisotropically conductive member.
[0081] [Protrusion process] The protruding step is a step performed after the polishing step in which the conductive paths are caused to protrude from at least one of the one surface and the other surface of the insulating base material. As a specific example, a part of the anodic oxide film 44 is removed. To remove a part of the anodic oxide film 44, for example, an acidic or alkaline aqueous solution that dissolves the anodic oxide film 44, i.e., aluminum oxide (Al2O3), without dissolving the metal constituting the conductive path 22 is used. The acidic or alkaline aqueous solution is made into droplets and brought into contact with the anodic oxide film 44 having the pores 21 filled with metal, thereby removing a part of the anodic oxide film 44. As a method for bringing the acidic or alkaline aqueous solution into droplets and bringing it into contact with the anodic oxide film 44, a spray etching method is used in which the dissolving solution is made into droplets as described above and sprayed onto the insulating base material, i.e., the anodic oxide film 44.
[0082] When using an aqueous acid solution, it is preferable to use an aqueous solution of an inorganic acid such as sulfuric acid, phosphoric acid, nitric acid, or hydrochloric acid, or a mixture thereof. Among them, an aqueous solution not containing chromic acid is preferable from the viewpoint of excellent safety. The concentration of the aqueous acid solution is preferably 1 to 10 mass %. The temperature of the aqueous acid solution is preferably 25 to 60°C. In addition, when an alkaline aqueous solution is used, it is preferable to use an aqueous solution of at least one alkali selected from the group consisting of sodium hydroxide, potassium hydroxide, and lithium hydroxide. The concentration of the alkaline aqueous solution is preferably 0.1 to 5 mass %. The temperature of the alkaline aqueous solution is preferably 20 to 35°C. Specifically, for example, a 50 g / L, 40° C. aqueous phosphoric acid solution, a 0.5 g / L, 30° C. aqueous sodium hydroxide solution, or a 0.5 g / L, 30° C. aqueous potassium hydroxide solution are preferably used.
[0083] The immersion time in the acid or alkali aqueous solution is preferably 8 to 120 minutes, more preferably 10 to 90 minutes, and even more preferably 15 to 60 minutes. Here, the immersion time refers to the total immersion time when short immersion treatments are repeated. Note that a cleaning treatment may be performed between each immersion treatment.
[0084] Furthermore, the metal 45, i.e., the conductive path 22, is caused to protrude from the front surface 44a or the back surface 44b of the anodized film 44, but as described above, it is preferable that the conductive path 22 protrudes by 10 nm to 1000 nm from the front surface 44a or the back surface 44b of the anodized film 44. That is, the length h of the above-mentioned protrusion 22a in the thickness direction Dt is preferably 10 nm to 1000 nm, and more preferably 50 nm to 500 nm, in order to improve the bondability with the bonded member.
[0085] When the length h of the protruding portion of the conductive path 22 in the thickness direction Dt is to be strictly controlled, it is preferable to fill the inside of the pore 21 with a conductive material such as a metal, process the anodized film 44 and the end of the conductive material such as the metal so as to be flush with each other, and then selectively remove the insulating base material such as the anodized film. After the above-mentioned metal filling or protruding step, a heat treatment can be performed to reduce distortion in the conductive path 22 caused by the metal filling. The heat treatment is preferably carried out in a reducing atmosphere from the viewpoint of suppressing oxidation of the metal, and more specifically, is preferably carried out at an oxygen concentration of 20 Pa or less, and more preferably in a vacuum. Here, vacuum refers to a state of space in which at least one of the gas density and the air pressure is lower than that of the atmosphere. Moreover, the heat treatment is preferably performed while applying stress to the anodic oxide film 44 for the purpose of straightening.
[0086] [Resin layer forming process] In the step of forming the resin layer 18, for example, an inkjet method, a transfer method, a spray method, a screen printing method, or the like is used. The inkjet method is preferable because the resin layer 18 is directly formed on the insulating substrate 20, and therefore the step of forming the resin layer 18 can be simplified. The resin layer 18 can be formed, for example, using a conventionally known surface protection tape attachment device and laminator. In the step of forming the resin layer, a resin layer is formed on the entire surface of the insulating substrate. The resin material constituting the resin layer 18 is as described above.
[0087] In addition to the above-mentioned methods, examples of methods for forming the resin layer 18 include a method in which a resin composition containing an antioxidant material, a polymer material, a solvent (e.g., methyl ethyl ketone, etc.) described below is applied to the entire surface of the insulating substrate, dried, and optionally baked. The method for applying the resin composition is not particularly limited, and any conventionally known coating method can be used, such as gravure coating, reverse coating, die coating, blade coating, roll coating, air knife coating, screen coating, bar coating, and curtain coating. The drying method after coating is not particularly limited, and examples thereof include a heating treatment at a temperature of 0°C to 100°C in the atmosphere for several seconds to several tens of minutes, and a heating treatment at a temperature of 0°C to 80°C under reduced pressure for several tens of minutes to several hours. The method of baking after drying is not particularly limited as it varies depending on the polymer material used. When a polyimide resin is used, for example, a treatment of heating at a temperature of 160°C to 240°C for 2 minutes to 60 minutes can be mentioned, and when an epoxy resin is used, for example, a treatment of heating at a temperature of 30°C to 80°C for 2 minutes to 60 minutes can be mentioned.
[0088] The present invention is basically configured as described above. Although the anisotropically conductive member and joined body of the present invention have been described in detail above, the present invention is not limited to the above-mentioned embodiments, and various improvements and modifications may be made without departing from the spirit and scope of the present invention. EXAMPLES
[0089] The features of the present invention will be described in more detail below with reference to examples. The materials, reagents, amounts and ratios of substances, and operations shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the following examples. In this example, there were produced bonded bodies of Examples 1 to 12 and Comparative Examples 1 and 2. The sizes and the like of the bonded bodies of Examples 1 to 12 and Comparative Examples 1 and 2 are shown in Table 1 below. The bond strength and the state of the protrusions after bonding were evaluated for the bonded bodies of Examples 1 to 12 and the bonded bodies of Comparative Examples 1 and 2. The evaluation results of the bond strength and the state of the protrusions after bonding are shown in Table 2 below. Next, the bonding strength and the state of the protrusion after bonding will be described.
[0090] (Evaluation of bonding strength) The bond strength was evaluated by measuring the shear strength of the bond between the TEG chip, anisotropic conductive member, and interposer in each of the examples and comparative examples using a Stellar 4000 bond tester (manufactured by Nordson Advanced Technologies, Inc.). The bonding strength was calculated as the bonding strength value (MPa) per area of the TEG chip from the obtained breaking load. The bonding strength value was evaluated according to the following evaluation criteria. The evaluation results are shown in the bonding strength column in Table 2 below. Evaluation criteria A: 10MPa or less bonding strength value B: 3MPa≦bonding strength value<10MPa C: Bond strength value < 3MPa
[0091] <Preparation of junction for evaluation> A TEG chip (Test Element Group chip) with Cu pads and an interposer were prepared. The insulating layer was SiN. The step between the insulating layer and the Cu pad surface was 1 μm. The TEG chip had a chip size of 8 mm square, and the ratio of electrode area (copper post) to chip area was 25%. The interposer had a chip size of 10 mm square, as it included extraction wiring around the periphery. An anisotropic conductive member measuring 10 mm square was used. For bonding, the TEG chip, the anisotropic conductive material, and the interposer were stacked in this order, and temporarily bonded using a room temperature bonding device (WP-100 (model), manufactured by PMT Co., Ltd.) under the conditions of a heating temperature of 80°C, a time of 1 minute, and a pressure of 10 MPa. Next, the temporarily bonded samples were pressed at a pressure of 10 MPa using a room temperature bonding device (model: manufactured by PMT Co., Ltd.), and then permanently bonded at a heating temperature of 140° C. for 10 seconds. Next, the resin layer of the bonded sample was cured under the resin curing process conditions of a heating temperature of 250° C. for 180 seconds and a pressure of 10 MPa to prepare a bonded body for evaluation. A type 1 laminate configuration is one in which a TEG chip, an anisotropic conductive material, and an interposer are laminated in this order.
[0092] In addition, the TEG chip, the anisotropic conductive material, the TEG chip, the anisotropic conductive material and the interposer were stacked in this order, and temporarily bonded under the temporary bonding process conditions of a heating temperature of 80°C, a time of 1 minute and a pressure of 10 MPa using a room temperature bonding apparatus (WP-100 (model), manufactured by PMT Co., Ltd.) as described above. Next, the temporarily bonded samples were pressed at a pressure of 10 MPa using a room temperature bonding machine (model: manufactured by PMT Co., Ltd.), and then permanently bonded at a heating temperature of 140°C for 10 seconds. Next, the resin layer of the permanently bonded samples was cured under resin curing process conditions of a heating temperature of 250°C, 180 seconds, and a pressure of 10 MPa to produce a bonded body for evaluation. A type 2 laminate structure is one in which a TEG chip, an anisotropic conductive material, a TEG chip, an anisotropic conductive material, and an interposer are laminated in this order.
[0093] (Protruding part condition after joining) The state of the protrusion after bonding will be described. For each of the assemblies of the TEG chip, the anisotropic conductive member, and the interposer in each of the examples and comparative examples, the anodized film was cut in the thickness direction using a focused ion beam (FIB). Next, a field emission scanning electron microscope (S-4800 (model number) manufactured by Hitachi High-Technologies Corporation) was used to capture an image at a magnification of 100,000 times. In the captured images, 100 protrusions were identified. The 100 identified protrusions were judged for contact with adjacent protrusions. The state of the 100 identified protrusions after bonding was evaluated based on the presence or absence of contact with adjacent protrusions, according to the evaluation criteria shown below. The evaluation results are shown in the column for the state of the protrusion after bonding in Table 1 below. The state of the protrusion after bonding is an index for evaluating the degree of buckling of the protrusion. Evaluation criteria A: Of 100 protrusions, the number of protrusions that contact adjacent protrusions is 0 B: Of 100 protrusions, the number of protrusions that contact adjacent protrusions is 1 to 10 C: Of 100 protrusions, the number of protrusions that contact adjacent protrusions is 11 or more Regarding the presence or absence of contact with the adjacent protrusion, even partial contact with the adjacent protrusion was determined as contact.
[0094] Examples 1 to 12 and Comparative Examples 1 and 2 will be explained below. Example 1 A description will be given of a bonded body according to Example 1. In Example 1, an anodized aluminum film was used as the insulating base material. [Structure] <Preparation of aluminum substrate> A molten metal was prepared using an aluminum alloy containing 0.06 mass% Si, 0.30 mass% Fe, 0.005 mass% Cu, 0.001 mass% Mn, 0.001 mass% Mg, 0.001 mass% Zn, 0.001 mass% Ti, and the remainder being Al and unavoidable impurities. The molten metal was treated and filtered, and an ingot 500 mm thick and 1200 mm wide was produced using a DC (Direct Chill) casting method. Next, the surface was scraped off to an average thickness of 10 mm using a facing machine, and then the material was soaked at 550°C for approximately 5 hours. When the temperature had dropped to 400°C, the material was rolled into a 2.7 mm thick plate using a hot rolling machine. Further, the sheet was heat-treated at 500° C. using a continuous annealing machine, and then cold-rolled to a thickness of 1.0 mm to obtain an aluminum substrate of JIS 1050 material. The aluminum substrate was formed into a wafer having a diameter of 200 mm (8 inches), and then subjected to the following treatments.
[0095] <Electrolytic polishing treatment> The above-mentioned aluminum substrate was subjected to electrolytic polishing treatment using an electrolytic polishing solution having the following composition under conditions of a voltage of 25 V, a solution temperature of 65° C., and a solution flow rate of 3.0 m / min. The cathode was a carbon electrode, and the power supply was GP0110-30R (manufactured by Takasago Manufacturing Co., Ltd.) The flow rate of the electrolyte was measured using a vortex flow monitor FLM22-10PCW (manufactured by AS ONE Corporation).
[0096] (Electrolytic polishing liquid composition) 85% phosphoric acid (Fujifilm Wako Pure Chemical Corporation reagent) 660mL ·Pure water 160mL ·Sulfuric acid 150mL 30mL ethylene glycol
[0097] <Anodizing process> Next, the aluminum substrate after electrolytic polishing was subjected to anodizing treatment by a self-ordering method in accordance with the procedure described in JP-A-2007-204802. The aluminum substrate after electrolytic polishing was subjected to a pre-anodizing treatment for 5 hours in an electrolytic solution of 0.50 mol / L oxalic acid under conditions of a voltage of 40 V, a solution temperature of 16° C., and a solution flow rate of 3.0 m / min. Thereafter, the aluminum substrate after the pre-anodizing treatment was subjected to a coating removal treatment by immersing it in a mixed aqueous solution of 0.2 mol / L chromic anhydride and 0.6 mol / L phosphoric acid (liquid temperature: 50° C.) for 12 hours. Thereafter, the plate was subjected to a re-anodizing treatment for 10 hours in an electrolyte solution of 0.50 mol / L oxalic acid under conditions of a voltage of 40 V, a liquid temperature of 16° C., and a liquid flow rate of 3.0 m / min, to obtain an anodized film with a thickness of 80 μm. In both pre-anodizing and re-anodizing treatments, the cathode was a stainless steel electrode, and the power source was GP0110-30R (manufactured by Takasago Manufacturing Co., Ltd.). The cooling device was NeoCool BD36 (manufactured by Yamato Scientific Co., Ltd.), and the stirring and heating device was Pair Stirrer PS-100 (manufactured by EYELA Tokyo Rikakikai Co., Ltd.). Furthermore, the flow rate of the electrolyte was measured using a vortex flow monitor FLM22-10PCW (manufactured by AS ONE Corporation).
[0098] <Barrier layer removal process> Next, using the same treatment solution and treatment conditions as in the above-mentioned anodizing treatment, electrolysis (electrolytic removal treatment) was performed while continuously decreasing the voltage from 40 V to 0 V at a voltage decrease rate of 0.2 V / sec. Thereafter, an etching treatment (etching removal treatment) was performed by immersing the sample in 5 mass % phosphoric acid at 30°C for 30 minutes to remove the barrier layer at the bottom of the micropores of the anodized film, exposing the aluminum through the micropores.
[0099] Here, the average opening diameter of the micropores present in the anodized film after the barrier layer removal process was 60 nm. The average opening diameter was measured by taking a surface image at a magnification of 50,000 times using a field emission scanning electron microscope (FE-SEM), selecting 50 micropores from the surface image, and measuring the diameter of the opening of each of the 50 selected micropores. The average value of the diameters of the openings of the measured micropores was calculated. This average value was taken as the average opening diameter. The average thickness of the anodized film after the barrier layer removal process was 80 μm. The average thickness was measured by cutting the anodized film in the thickness direction using a focused ion beam (FIB), and then taking a cross-sectional image of the cross-section at a magnification of 50,000 times using a field emission scanning electron microscope (FE-SEM). In the cross-sectional image, the length of 10 points corresponding to the thickness of the anodized film was measured, and the average length of the 10 measured points was calculated. This average value was determined as the average thickness of the anodized film after the barrier layer removal process. The density of the micropores in the anodic oxide film is approximately 100 million / mm 2The micropore density was measured and calculated by the method described in paragraphs
[0168] and
[0169] of JP2008-270158A. The degree of ordering of the micropores in the anodic oxide film was 92%. The degree of ordering was measured and calculated by taking a surface image at a magnification of 20,000 times using a field emission scanning electron microscope (FE-SEM) and measuring it using the method described in paragraphs
[0024] to
[0027] of JP2008-270158A.
[0100] <Metal filling process> Next, electrolytic plating was carried out by using the aluminum substrate as the cathode and platinum as the anode. Specifically, a copper plating solution having the composition shown below was used and constant current electrolysis was performed to produce a metal-filled microstructure in which copper was filled into the inside of the pores (micropores) to form conductive paths. Here, constant current electrolysis was performed using a plating device manufactured by Yamamoto Plating Tester Co., Ltd. and a power supply (HZ-3000) manufactured by Hokuto Denko Corporation. After cyclic voltammetry was performed in the plating solution to confirm the deposition potential, the treatment was performed under the conditions shown below. (Copper plating solution composition and conditions) ·Copper sulfate 100g / L ·Sulfuric acid 50g / L Hydrochloric acid 15g / L ·Temperature 25℃ ·Current density 10A / dm 2
[0101] <Polishing process> Next, the surface of the metal-filled microstructure in which the conductive paths were formed by filling the metal was subjected to CMP treatment and polished 5 μm from the surface to smooth the surface. As the CMP slurry, PNANERLITE-7000 manufactured by Fujimi Inc. was used. The surface of the anodized film after filling the pores (micropores) with metal was observed with a field emission scanning electron microscope (FE-SEM) to determine whether 1,000 micropores were sealed with metal. The sealing rate (number of sealed micropores / 1,000) was calculated to be 96%. In addition, after filling the pores (micropores) with metal, the anodized film was cut in the thickness direction using an FIB, and cross-sectional images were taken of the cross-section at a magnification of 50,000 times using a field emission scanning electron microscope (FE-SEM).When the inside of the pores (micropores) was examined, it was found that the inside of the sealed pores (micropores) was completely filled with metal.
[0102] <Trimming process> The metal-filled microstructure after the polishing process was sprayed with droplets of sodium hydroxide solution (concentration: 5% by mass, liquid temperature: 20°C) onto the surface of the anodized film by spray etching. The amount of sodium hydroxide solution sprayed was adjusted so that the arithmetic mean distance δ (see Fig. 3) in the thickness direction was 100 nm, and the surface of the aluminum anodized film was selectively dissolved. The structure was then washed with water and dried to protrude the copper cylinders that act as conductive paths. As a result, the length h of the protrusions (see Fig. 1) was 300 nm. For the spray etching, ADE-3000S (product name) manufactured by Actes Kyosan Co., Ltd. was used. The arithmetic mean distance δ (see FIG. 3) in the thickness direction on the surface side of the anodic oxide film was measured using the captured image as described above.
[0103] <Substrate removal process> Next, the aluminum substrate was dissolved and removed by immersing it in a 20% by mass aqueous solution of mercury chloride (mercuric chloride) at 20° C. for 3 hours to prepare a structure.
[0104] <Polishing process> Next, the rear surface of the anodized film formed by removing the aluminum substrate of the structure was subjected to CMP processing to smooth the metal-filled microstructure. As the CMP slurry, PNANERLITE-7000 manufactured by Fujimi Inc. was used.
[0105] <Trimming process> After the polishing process, a sodium hydroxide solution (concentration: 5 mass%, liquid temperature: 20°C) was sprayed in droplets onto the back surface of the anodized film of the structure using a spray etching method. The amount of sodium hydroxide solution sprayed was adjusted so that the arithmetic mean distance δ (see Figure 3) in the thickness direction described above was 100 nm, and the surface of the aluminum anodized film was selectively dissolved. The structure was then washed with water and dried, causing the copper cylinders that served as the conductive paths to protrude. As a result, the length h of the protrusions described above (see Figure 1) was 300 nm. For the spray etching, ADE-3000S (product name) manufactured by Actes Kyosan Co., Ltd. was used. The arithmetic mean distance δ in the thickness direction on the back surface side of the anodic oxide film was measured using the photographed image as described above.
[0106] <Resin layer formation process> After the trimming process, resin layers were formed on the front and back surfaces of the anodized film of the structure by the method described below, to prepare an anisotropic conductive bonding member. The resin layer was formed using a resin composition containing a non-conductive epoxy thermosetting resin (BST001A, curing temperature 150°C, manufactured by Namics Corporation) and diethylene glycol diethyl ether as a dilution solvent by adjusting the rotation speed of a spin coater so as to obtain a thickness of 1.5 μm. Next, the anisotropic conductive bonding member thus produced was cut into a size of 10 mm square. DAD3230 (product name) manufactured by Disco Corporation was used for cutting the anisotropic conductive member.
[0107] The above-mentioned arithmetic mean distance δ was calculated as follows. The anisotropically conductive member thus produced is cut using a focused ion beam (FIB) to expose a cross section in the thickness direction of the anodized film, which is the insulating base material. Next, a cross section of the anodic oxide film in the thickness direction is photographed with a field emission scanning electron microscope (FE-SEM) to obtain an image at a magnification of 150k. In the captured image, a reference point Pb (see FIG. 3) was set at an arbitrary position on the back surface 20b side opposite to the front surface 20a of the insulating substrate 20. A reference line Ls (see FIG. 3) was set parallel to the direction x and passing through the reference point Pb. Next, from among the points corresponding to the apexes Pc (see FIG. 3) in the captured image, the 10 apexes Pc were selected in ascending order of their position relative to the reference line Ls. Also, from among the points corresponding to the contact points Vc (see FIG. 3), the 10 contact points Vc were selected in descending order of their position relative to the reference line Ls. In the captured image, the distance from the reference line Ls to each of the points corresponding to the selected 10 apexes Pc was calculated. The average of the 10 distances between the reference line Ls and the points corresponding to the 10 apexes Pc was calculated using the least squares method. The average value calculated using the least squares method is shown as a point on the captured image. A line Lc (see Figure 3) parallel to the direction x passing through the point indicating the average value of the apexes Pc was calculated. In the captured image, the distance from the reference line Ls was calculated for each of the points corresponding to the selected 10 contact areas Vc. The average of the 10 distances between the reference line Ls and the points corresponding to the 10 contact areas Vc was calculated using the least squares method. The average value calculated using the least squares method was displayed as a point on the captured image. A line Lb (see Figure 3) parallel to the direction x passing through the point indicating the average value of the contact areas Vc was calculated. Next, the distance between the parallel line Lc and the parallel line Lb in the thickness direction Dt was obtained to obtain the arithmetic mean distance δ.
[0108] Example 2 Example 2 differs from Example 1 in that the amount of sodium oxide solution sprayed was adjusted so that the arithmetic mean distance δ (see FIG. 3) in the thickness direction on both the front and back sides of the anodized film was 20 nm, selectively dissolving the front and back sides of the anodized film of aluminum. Example 3 Example 3 is different from Example 1 in that the amount of sodium oxide aqueous solution sprayed was adjusted so that the arithmetic mean distance δ (see FIG. 3) in the thickness direction on both the front and back sides of the anodized film was 60 nm, thereby selectively dissolving the front and back sides of the anodized film of aluminum. Example 4 Example 4 differs from Example 1 in that the amount of sodium oxide solution sprayed was adjusted so that the arithmetic mean distance δ (see FIG. 3) in the thickness direction on both the front and back sides of the anodized film was 5 nm, thereby selectively dissolving the front and back sides of the anodized film of aluminum. Example 5 Example 5 differs from Example 3 in that the resin is on the CNP surface, and is otherwise the same as Example 2. Note that "having the resin on the CNP surface" refers to a state in which the epoxy resin is applied onto the protruding portion of the anisotropically conductive member. Example 6 Example 6 differs from Example 3 in that resin is present on the electrode surface, and other than that, it is the same as Example 2. Note that "resin is present on the electrode surface" refers to a state in which epoxy resin is applied onto the Cu pad surface of the TEG chip.
[0109] Example 7 Example 7 differs from Example 2 in that the conductive paths are made of Ni, but otherwise is the same as Example 2. The conductive path was formed by electrolytic plating using a mixed solution of nickel sulfate / nickel chloride / boric acid = 300 / 60 / 40 (g / L) as the electrolyte, a nickel electrode as the cathode, and a platinum electrode as the anode. In the electrolytic plating process, the electrolyte was kept at a temperature of 50°C and constant current electrolysis (5A / dm 2 ) was carried out. Example 8 Example 8 differs from Example 2 in that the length h of the protrusion (see FIG. 1) was set to 10,000 nm, but otherwise was the same as Example 2. Example 9 Example 9 was different from Example 2 in that the length h (see FIG. 1) of the protrusion was set to 3 nm, but otherwise was the same as Example 2. Example 10 Example 10 was different from Example 3 in that the size of the TEG chip was 4 mm square, but otherwise was the same as Example 3. Example 11 Example 11 was different from Example 3 in that the size of the anisotropically conductive member was 8 mm square, but otherwise was the same as Example 3. Example 12 Example 12 differs from Example 3 in that it uses a Type 2 stacking configuration in which a TEG chip, an anisotropic conductive material, a TEG chip, an anisotropic conductive material, and an interposer are stacked in that order, and the size of the anisotropic conductive material is 8 mm square. Otherwise, it is the same as Example 3.
[0110] Comparative Example 1 Comparative Example 1 differs from Example 1 in that all the trimming steps described above were performed using a dipping method instead of a spray etching method. Furthermore, Comparative Example 1 differs in that the temporarily bonded samples were pressurized at a pressure of 10 MPa using a room temperature bonding device ((type), manufactured by PMT Co., Ltd.), and then permanently bonded at a heating temperature of 120°C for 10 seconds. Other than these, the comparative example was the same as Example 1. In Comparative Example 1, the arithmetic mean distance δ in the thickness direction (see FIG. 3) was 1 nm.
[0111] Comparative Example 2 Comparative Example 2 differs from Example 1 in that the amount of sodium oxide aqueous solution sprayed was adjusted so that the arithmetic mean distance δ (see FIG. 3) in the thickness direction on both the front and back sides of the anodized film was 250 nm, selectively dissolving the front and back sides of the anodized film of aluminum.
[0112] [Table 1]
[0113] [Table 2]
[0114] As shown in Table 2, in comparison with Comparative Example 1 and Comparative Example 2, Examples 1 to 12 were excellent in terms of bonding strength and the state of the protruding portion after bonding. In Comparative Example 1, the arithmetic mean distance δ was short, the bonding strength was low, and many protrusions were in contact with adjacent protrusions. In Comparative Example 2, the arithmetic mean distance δ was long, and many protrusions were in contact with adjacent protrusions. Among Examples 1 to 12, Examples 2, 3, 5, 6, 10 and 11 were superior in bonding strength and state of the protruding portion after bonding. From Examples 1 to 4, when the arithmetic mean distance δ was 20 to 100 nm, the bonding strength and the state of the protrusion after bonding were superior, and when it was 20 to 60 nm, the bonding strength and the state of the protrusion after bonding were even superior. From Examples 2 and 7, it was found that the conductive paths made of Cu were superior to those made of Ni in terms of bonding strength and state of the protrusions after bonding. From Example 2, Example 8, and Example 9, Example 2 in which the protrusion was 300 nm had better bonding strength and the state of the protrusion after bonding. [Explanation of symbols]
[0115] 10 Anisotropic conductive material 12, 13 zygote 18 Resin layer 20 Insulating substrate 20a, 24a, 40a, 32a, 34a, 37a, 44a surface 20b, 44b back side 20d recess 21 Pore 22 Conduction Path 22a, 22b protrusion 22c side 24 Resin layer 30, 31 Semiconductor elements 32, 37 Element substrate 33 Resin layer 34, 35, 38 electrodes 36 Insulating layer 39 Insulating layer 40 Aluminum substrate 42c bottom 42d side 43 Barrier Layer 44 Anodic oxide film 45, 45b metal 45a metal layer Dt Thickness direction Ls reference line Pb reference point PC top Vc contact part d average diameter hm average thickness ht Thickness p Center distance x direction δ arithmetic mean distance w Interval
Claims
1. An insulating base material having electrical insulation properties; a plurality of conductive paths that penetrate the insulating base material in a thickness direction, are provided in a state in which they are electrically insulated from one another, and have protrusions that protrude from at least one surface of the insulating base material; in a cross section in the thickness direction of the insulating base material, the surface of the insulating base material from which the protruding portions of the conductive paths protrude has a plurality of apexes, and each of the plurality of protruding portions has a contact portion in contact with the insulating base material; an arithmetic average distance between the plurality of contact portions and the plurality of apexes in the thickness direction is 2 nm to 200 nm; the conductive path is made of Cu, Au or Al; where d is a diameter of the protrusion and h is a length of the protrusion in the thickness direction of the insulating base, d / h is 0.1 to 20; The anisotropically conductive member has a length of the protrusion in the thickness direction of the insulating substrate of 6 to 6000 nm.
2. A bonded body in which an anisotropic conductive member and a bonded member are bonded, A resin is filled between the anisotropic conductive member and the member to be joined, The anisotropically conductive member includes an insulating base material having electrical insulation properties, a plurality of conductive paths that penetrate the insulating base material in a thickness direction, are provided in a state in which they are electrically insulated from one another, and have protrusions that protrude from at least one surface of the insulating base material; in a cross section in the thickness direction of the insulating base material, the surface of the insulating base material from which the protruding portions of the conductive paths protrude has a plurality of apexes, and each of the plurality of protruding portions has a contact portion in contact with the insulating base material; an arithmetic average distance between the plurality of contact portions and the plurality of apexes in the thickness direction is 2 nm to 200 nm; the conductive path is made of Cu, Au or Al; where d is a diameter of the protrusion and h is a length of the protrusion in the thickness direction of the insulating base, d / h is 0.1 to 20; The length of the protrusion in the thickness direction of the insulating base material is 6 to 6000 nm.
3. The joined body according to claim 2 , wherein the members to be joined have a metal layer and a resin layer, and the metal layer is exposed from the resin layer.
4. The bonded body according to claim 3 , wherein the bonded members have a plurality of the metal layers, and at least one of the plurality of metal layers has a different height.
5. 4. The joined body according to claim 3, wherein the joined members have a joining surface on which a plurality of metal layers are provided, and the area of the joining surface is larger than the area of the surface from which the protruding portion of the anisotropically conductive member protrudes.
Citation Information
Patent Citations
Method for manufacturing multilayer wiring board
JP2018037509A
Method for producing carbon nanotube / resin composite, and carbon nanotube / resin composite
JP2019043001A
Anisotropic conductive member, manufacturing method for the same, structure, and manufacturing method for the same
JP2023069883A
Method of manufacturing bonded body, temporary-fixing member, and stacked body
WO2019163575A1